STRATEGI PENETAPAN HARGA KELAPA SAWIT PETANI PLASMA PADA PT. ADINUSA CAKRA MANDIRI DI KECAMATAN SEPAUK KABUPATEN SINTANG - Darmansah (Universitas Kapuas Sintang, 2024)
The pricing of Fresh Fruit Bunches (FFB) (palm fruit can be aimed at protecting plasma farmers such as setting a basic price so that price certainty for farmers is obtained and production incentives are obtained as well as to protect consumers through the determination of the highest price in accordance with the price in the market. Suggestions for this research: It is better to maintain the quality of oil palm fresh fruit bunches (FFB) in plantations owned by plasma farmers at PT. Adinusa Cakra Mandiri In Sepauk District, the company must continue to help in the selection of plasma oil palm land so that the fruit continues to be of high quality. The determination of palm FFB prices should be socialized to farmers who own plasma land through the company's partner cooperatives. Keywords: Determination Strategy, Palm Oil Price